2011
DOI: 10.1007/s12274-011-0101-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and enhanced photocatalytic activity of regularly shaped Cu2O nanowire polyhedra

Abstract: A series of unique nanowire superstructures, Cu 2 O nanowire polyhedra, have been synthesized through a cost-effective hydrothermal route. Three types of nanowire polyhedra, namely octahedra, concave octahedra, and hexapods, were formed in high morphological yields (90%) by reducing cupric acetate with o-anisidine or o-phenetidine in the presence of carboxylic acids. The architectures of these Cu 2 O nanowire polyhedra were examined by electron microscopy, which revealed ordered, highly aligned Cu 2 O nanowire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
71
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 47 publications
4
71
0
Order By: Relevance
“…This suggests that chemisorbed AO 7 is in the azo form ( Fig. S- [16,38]. de Jongh et al [7] reported that Cu 2 O is not an effective photocatalyst for water splitting but could reduce dissolved oxygen to H 2 O 2 , and Shi et al [16] recently proposed that the formation of H 2 O 2 in this way is responsible for the photodegradation of dye molecules over Cu 2 O.…”
Section: Chemisorption and Photocatalytic Activity Of Cu 2 O-au Nanocmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that chemisorbed AO 7 is in the azo form ( Fig. S- [16,38]. de Jongh et al [7] reported that Cu 2 O is not an effective photocatalyst for water splitting but could reduce dissolved oxygen to H 2 O 2 , and Shi et al [16] recently proposed that the formation of H 2 O 2 in this way is responsible for the photodegradation of dye molecules over Cu 2 O.…”
Section: Chemisorption and Photocatalytic Activity Of Cu 2 O-au Nanocmentioning
confidence: 99%
“…S- [16,38]. de Jongh et al [7] reported that Cu 2 O is not an effective photocatalyst for water splitting but could reduce dissolved oxygen to H 2 O 2 , and Shi et al [16] recently proposed that the formation of H 2 O 2 in this way is responsible for the photodegradation of dye molecules over Cu 2 O. Meanwhile, involvement of the so-called semiconductormediated photodegradation (SMPD) mechanism [50], in which absorption of light by the chemisorbed dye molecule generates an excited state from which it injects an electron into the conduction band of a semiconductor and is thereby oxidized, cannot be ruled out.…”
Section: Chemisorption and Photocatalytic Activity Of Cu 2 O-au Nanocmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of Cu 2 O micro or nanostructures with controllable morphologies has been developed [14,15], including nanocubes [15,16], octahedra [15,16], polyhedral morphology [17], hollow structures [18] and nanowires [19], and many growth mechanisms have been proposed. These Cu 2 O microcrystals were generally synthesized by hydrothermal methods in the presence of different capping reagents (e.g., surfactant [20], ascorbic acid or hydrazine hydrate [16], and acetic acid [17]).…”
Section: Introductionmentioning
confidence: 99%